Art therapy, trauma and neuroscience : theoretical and practical perspectives - King, Juliet L. (New York, NY : Routledge, 2022)
"Art Therapy, Trauma, and Neuroscience combines theory, research, and practice with traumatized populations in a neuroscience framework. The classic edition includes a new preface from the author discussing advances in the field. Recognizing the importance of a neuroscience- and trauma-informed approach to art therapy practice, research, and education, some of the most renowned figures in art therapy and trauma use translational and integrative neuroscience to provide theoretical and applied techniques for use in clinical practice. Graduate students, therapists, and educators will come away from this book with a refined understanding of brain-based interventions in a dynamic yet accessible format"--
Keywords: Brain damage -- Patients -- Rehabilitation; Brain -- Wounds and injuries -- Patients -- Rehabilitation; Art therapy -- Methodology; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Psychopathology / Post-Traumatic Stress Disorder (PTSD)